Acupuncture for lateral epicondylitis (tennis elbow): study protocol for a randomized, practitioner-assessor blinded, controlled pilot clinical trial - Shin, Kyung-Min (BioMed Central, 2013)
BACKGROUND: Lateral epicondylitis is the most frequent cause of pain around the elbow joint. It causes pain in the region of the elbow joint and results in dysfunction of the elbow and deterioration of the quality of life. The purpose of this study is to compare the effects of ipsilateral acupuncture, contralateral acupuncture and sham acupuncture on lateral epicondylitis. METHODS/DESIGN: Forty-five subjects with lateral epicondylitis will be randomized into three groups: the ipsilateral acupuncture group, contralateral acupuncture group and the sham acupuncture group. The inclusion criteria will be as follows: (1) age between 19 and 65 years with pain due to one-sided lateral epicondylitis that persisted for at least four weeks, (2) with tenderness on pressure limited to regions around the elbow joint, (3) complaining of pain during resistive extension of the middle finger or the wrist, (4) with average pain of NRS 4 or higher during the last one week at a screening visit and (5) voluntarily agree to this study and sign a written consent. Acupuncture treatment will be given 10 times in total for 4 weeks to all groups. Follow up observations will be conducted after the completion of the treatment, 8 weeks and 12 weeks after the random assignment. Ipsilateral acupuncture group and contralateral acupuncture group will receive acupuncture on LI4, TE5, LI10, LI11, LU5, LI12 and two Ashi points. The sham acupuncture group will receive treatment on acupuncture points not related to the lateral epicondylitis using a non-invasive method. The needles will be maintained for 20 minutes. The primary outcome will be differences in the visual analogue scale (VAS) for elbow pain between the groups. The secondary outcome will be differences in patient-rated tennis elbow evaluation (PRTEE), pain-free/maximum grip strength (Dynamometer), pressure pain threshold, clinically relevant improvement, patient global assessment, and the EQ-5D. The data will be analyzed with the paired t-test and ANCOVA (P <0.05). DISCUSSION: The results of this study will allow evaluation of contralateral acupuncture from two aspects. First, if the contralateral acupuncture shows the effects similar to ipsilateral acupuncture, this will establish clinical basis for contralateral acupuncture. Second, if the effects of contralateral acupuncture are not comparable to the effects of ipsilateral acupuncture, but are shown to be similar to the effects of the sham acupuncture, we can establish the basis for using the same acupoints of the unaffected side as a control in acupuncture clinical studies. TRIAL REGISTRATION: This trial has been registered with the ‘Clinical Research Information Service (CRIS)’, Republic of Korea: KCT0000628.